Implementation of the Principle of Qaulan Karīmah in the Development of Adolescent Morals at the Al-Jam'iyatul Washliyah Orphanage: A Study of Islamic Communication - Manita Rahma Hasibuan; Muktaruddin (Program Studi Komunikasi dan Penyiaran Islam Fakultas Dakwah Universitas Islam Internasional Darullughah Wadda'wah Bangil Pasuruan, 2025)
This study aims to explore how the principle of Qaulan Karimah is implemented in shaping the character of adolescents at the Al-Jam'iyatul Washliyah Orphanage in Pulo Brayan, Medan. Qaulan Karimah is an Islamic communication principle that emphasizes noble and kind speech, serving as a fundamental guideline in developing the personality and morals of the adolescents within the orphanage environment. The method used is a descriptive qualitative approach, with data collected through in-depth interviews, direct observation, and documentation. The informants in this study consist of six individuals, including caregivers and teachers who are actively involved in guiding the adolescents. Data analysis was carried out through data reduction, data presentation, and drawing conclusions inductively. The findings show that the implementation of the Qaulan Karimah principle has a positive impact on the moral development of adolescents, such as increased patience, the ability to speak politely, and the emergence of a more positive attitude toward others. This implementation is supported by regular religious activities such as Quranic recitations, congregational prayers, and Islamic character development programs. Although there are challenges, such as the diverse backgrounds of the adolescents and consistency in applying the principle, the approach has proven effective in moral development. The implication of this study is that the use of Islamic communication principles like Qaulan Karimah can serve as an effective strategy for character building among adolescents, especially in social institutions such as orphanages. Keywords: Implementation, Qaulan Karimah, Adolescent Morals, Orphanage.